1990
DOI: 10.1111/j.1432-1033.1990.tb19108.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and genetic analysis of a maltopentaose‐producing amylase from an alkaliphilic Gram‐positive bacterium

Abstract: Two amylases have been purified from the culture fluid of an alkaliphilic bacterium. Amylase A-60 consists of a single type of polypeptide chain of 60 kDa and exhibits an a-amylase-type of starch cleavage. Amylase A-180 is approximately 180 kDa in size, represents the largest exoenzyme so far identified in prokaryotes and in the initial enzyme reaction cleaves starch exclusively to maltopentaose. A-60 and A-1 80 are immunologically unrelated enzymes. The structural gene for amylase A-180 has been cloned and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…We have now found the motif in several other published sequences of bacterial carbohydrases, including the sequences of a poly(3-hydroxybutyrate) depolymerase from Alcaligenesfaecalis (23), an exo-poly-a-D-galacturonosidase from Erwinia chrysamthemi (24), a bifunctional a-amylase-pullulanase from Clostridium thermohydrosulfuricum (25), and a maltopentaose-producing amylase from an alkaliphilic Gram-positive bacterium (26). The resemblance to Fn3 units was not described in any of these latter reports (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 93%
“…We have now found the motif in several other published sequences of bacterial carbohydrases, including the sequences of a poly(3-hydroxybutyrate) depolymerase from Alcaligenesfaecalis (23), an exo-poly-a-D-galacturonosidase from Erwinia chrysamthemi (24), a bifunctional a-amylase-pullulanase from Clostridium thermohydrosulfuricum (25), and a maltopentaose-producing amylase from an alkaliphilic Gram-positive bacterium (26). The resemblance to Fn3 units was not described in any of these latter reports (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 93%
“…The chitinase secreted by E. coli DH5␣FЈ/pCHIBT showed hydrolytic activity against the chitin tetrameric derivative (4-MU-(GlcNAc) 3 ], just a slight activity against the trimeric derivative [(4-MU-(GlcNAc) 2 ], and practically no activity against the dimeric derivative (4-MU-GlcNAc) ( Table 1) when tested at pH 6. These data indicate that ChiA74 is an endochitinase (5,22).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the highly conserved aromatic amino acids Trp-171, Phe-177, and Trp- In relation to the second domain, this region shows homology to fibronectin type III. This protein was initially found in mammals and forms extracellular, multifunctional matrices which are important in cell bonding (28); however, it is believed that it was horizontally transferred to prokaryotes, and now it is found in bacterial chitinases, cellulases, and amylases (3,23,32). Because of the bonding action of fibronectin, its presence in these enzymes may be related to the substrate attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Fi bronec tin-t ype-111-like sequences have also been found in endoglucanase B from C. jimi as three randem repeats (Meinke et al, 1991b). Homology analysis showed that domain 3 of chitinase C was similar not only to these sequences but also to amylase A-180 from an alkaliphilic eubacterium and poly(3-hydroxybutyrate) depolymerase from Alcaligenes faeqalis (Candussio et al, 1990;Saito et al, 1989). Thirteen out of 93 amino acids (14.0%) were identical in these sequences.…”
Section: Efcqdy-l I Taavtadgsdcgk I Daadyceasky I Dwynvnty Dffgaia--kmentioning
confidence: 97%